Homeland Security: Establishment and Implementation of the United States Northern Command - Bowman, Steve (Library of Congress. Congressional Research Service., 2006)
The Department of Defense (DOD) established U.S. Northern Command (NORTHCOM) to fight terrorism at home. Significant organizational and procedural progress has been made in setting up this organization. However, questions remain concerning interagency relationships and information sharing.